Gerenciamento de portfólio de projetos: uma abordagem para investimentos correntes e de melhoria - Felipe Luz Barbosa de Castro (2014)
This article aims to the development of a methodology to prioritize a portfólio of projects. The proposed methodology aims to capture peculiar characteristics of sustain investments, like interdependence and multiple objectives, which have been ignored by the most common methods usually applied, e. g., financial and scoring methods, as well to reduce the efforts used to estimate the expected gains in each proposed project. The study was developed through the application of non-exact optimization techniques and stochastic computer simulation by discrete events. Thus, its implantation demands specific knowledge of these operational research techniques applied to the industry of interest. To validate this work, this methodology was tested in hypothetical scenery in a typical loading and hauling processes for open pit mining operations using data of a strong global player in the iron ore market. The developed model proved itself to be suitable to the mining industry, with possibilities to be replied to other industrial branches, mainly in manufacturing chains, where the application of algebraic methods are less feasible and the best way to represent the company processes is the computational simulation. During the work it was identified that the development of another heuristic to the same simulation model can help to identify the bottlenecks in the productive process as well the better points for which the development of new projects would be more interesting.